Intelligent energy saving measurement method and realization of power grid based on IoT - Dapin ZHANG; Qinghai OU; Yeshen HE; Yiying ZHANG (Dianxin kexue)
Power grid energy saving engineering,especially transmission and transformation related projects,is an important link of energy saving.The energy saving measurement methods of the main links of transmission and transformation were summarized,including IPMVP method and general energy saving measurement method in China.At the same time,by using the technology of IoT and fusion of relevant algorithms,the efficiency of measuring equipment can be improved,and the energy saving can be measured in a timely and accurate way.The calculation and measurement methods of energy saving were illustrated by an example,which provided a theoretical basis for energy saving measurement in power grid enterprises.